Fatty acid filled polyaniline nanofibres with dual electrical conductivity and thermo-regulatory characteristics: Futuristic material for thermal energy storage - Tanwar Surya; Varshney Gunjan; Kaur Raminder (e-Polymers)
This study emphasizes on the production of nano-encapsulated phase change materials for the application of thermal energy storage (TES). The core is undecylenic acid (UA), a renewable latent heat storage material, which is encased inside the polyaniline (PANI) nanofibres (NFs) synthesized by interfacial polymerization technique. The morphological and structural features of the prepared NFs were examined by high-resolution transmission electron microscopy and Fourier transform infrared spectroscopy. According to differential scanning calorimetry analysis, the latent heat values were observed as 56 ± 1.4 and 57 ± 1.3 J·g−1, while the melting and freezing temperatures were recorded as 18 ± 0.2°C and 14 ± 0.3°C, respectively. Thermogravimetric analysis revealed a multi-step deterioration pattern, demonstrating the developed nano-encapsulated-phase change material’s (PCMs’) exceptional thermal stability. In addition to exhibiting reliable thermal performance over numerous cycles, PANI/UA NFs showed excellent TES and release rates. This work addresses key challenges in TES applications by introducing a PCM based on renewable materials that offers enhanced thermal reliability and efficiency. The results contribute in the development of compact and environmentally friendly thermal management systems for utilizing in the applications of electronic device cooling, building energy systems, and renewable energy storage.